2020
DOI: 10.1186/s40337-020-00317-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between eating behavior and quarantine/confinement stressors during the coronavirus disease 2019 outbreak

Abstract: Background: Quarantine/confinement is an effective measure to face the Coronavirus disease 2019 (COVID-19). Consequently, in response to this stressful situation, people confined to their homes may change their everyday eating behavior. Therefore, the primary objective of this study is to evaluate the association between quarantine/ confinement stressors and eating behavior during the COVID-19 outbreak. The secondary objective is to compare the association of quarantine/confinement stressors and diet behavior … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
79
3
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 50 publications
15
79
3
7
Order By: Relevance
“…The objective of this analysis was to characterize the impact of the COVID-19 pandemic on disordered eating behavior using inductive, thematic analysis of ED-related Reddit forums. Consistent with previous investigations [ 7 - 12 , 24 , 25 , 30 ], our findings indicate that the COVID-19 pandemic and associated public health prevention measures negatively impacted the psychiatric health of most users. Users frequently sought comfort in a time of heighted emotional distress by engaging in ED behavior, which was exacerbated by abrupt and involuntary changes in daily routine, exposure to food shortages and panic buying, closure of exercise facilities, and reduced access to care and social support networks.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The objective of this analysis was to characterize the impact of the COVID-19 pandemic on disordered eating behavior using inductive, thematic analysis of ED-related Reddit forums. Consistent with previous investigations [ 7 - 12 , 24 , 25 , 30 ], our findings indicate that the COVID-19 pandemic and associated public health prevention measures negatively impacted the psychiatric health of most users. Users frequently sought comfort in a time of heighted emotional distress by engaging in ED behavior, which was exacerbated by abrupt and involuntary changes in daily routine, exposure to food shortages and panic buying, closure of exercise facilities, and reduced access to care and social support networks.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, Rodgers and colleagues [ 13 ] hypothesize that restriction may occur via reduced purchasing of specific food items and reluctance to leave home to purchase groceries given one’s fear of contagion. A positive association between fear of COVID-19, eating restraint, and concerns related to weight or shape emerged from an investigation among both the general population and individuals attending diet clinics for weight loss management [ 25 ]. Grocery shopping during the pandemic may prove difficult for those with disordered eating.…”
Section: Introductionmentioning
confidence: 99%
“…These data are not surprising. In the literature, indeed, it is well known that during home confinement people tend to increase their food intake [ 10 , 11 ]. A quarter of the Italian population consumed more food and one third increased time spent cooking at home [ 12 ], while an Italian study showed that half of the sample felt anxious about their eating habits, consumed comfort food and were inclined to increase food intake to feel better [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ED are in fact considered highly fragile due to the associated psychiatric comorbidities and metabolic anomalies [2]. Such elevated vulnerability makes them particularly susceptible to stress [2,3]. The COVID-19 pandemic and the consequent lockdown have been a great element of stress which worsened dysfunctional behaviors among ED patients [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Such elevated vulnerability makes them particularly susceptible to stress [ 2 , 3 ]. The COVID-19 pandemic and the consequent lockdown have been a great element of stress which worsened dysfunctional behaviors among ED patients [ 3 5 ]. As reported by Termorshuizen and colleagues in a study conducted in the United States and Netherland, during the COVID-19 pandemic, restriction practices increased among patients with anorexia nervosa, while binge-eating episodes augmented among those with bulimia nervosa and binge eating disorders [ 4 ].…”
Section: Introductionmentioning
confidence: 99%